2021
DOI: 10.1021/acs.jpcb.0c10970
|View full text |Cite
|
Sign up to set email alerts
|

Is a Dissociation Process Underlying the Molecular Origin of the Debye Process in Monohydroxy Alcohols?

Abstract: Herein, we investigated the molecular dynamics as well as intramolecular interactions in two primary monohydroxy alcohols (MA), 2-ethyl-1-hexanol (2EHOH) and n -butanol ( n BOH), by means of broad-band dielectric (BDS) and Fourier transform infrared (FTIR) spectroscopy. The modeling data obtained from dielectric studies within the Rubinstein approach [ Macromolecules 2013 46 7525 7541 ] originally developed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…1) using the combination of the Rubinstein model (RM) 30 supported by the van't Hoff analysis. 29,31 Herein, it should be briefly reminded that previous studies performed on a series of phenyl alcohols indicated that the presence of the phenyl group introduced the additional dispersive interactions (i.e., London dispersion forces and/or p-stacking 32,33 ) within the chosen materials, the interplay of which with the H-bonding changes along the separation between the phenyl and hydroxyl moieties. 31 It was observed that some of their properties, i.e., the glass transition temperature, molar surface entropy, and the Kirkwood factor, change non-linearly with the elongation of the alkyl chain revealing the ''odd-even'' effect (see the chemical structure in Fig.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…1) using the combination of the Rubinstein model (RM) 30 supported by the van't Hoff analysis. 29,31 Herein, it should be briefly reminded that previous studies performed on a series of phenyl alcohols indicated that the presence of the phenyl group introduced the additional dispersive interactions (i.e., London dispersion forces and/or p-stacking 32,33 ) within the chosen materials, the interplay of which with the H-bonding changes along the separation between the phenyl and hydroxyl moieties. 31 It was observed that some of their properties, i.e., the glass transition temperature, molar surface entropy, and the Kirkwood factor, change non-linearly with the elongation of the alkyl chain revealing the ''odd-even'' effect (see the chemical structure in Fig.…”
Section: Introductionmentioning
confidence: 98%
“…1) using the combination of the Rubinstein model (RM) 30 supported by the van’t Hoff analysis. 29,31 Herein, it should be briefly reminded that previous studies performed on a series of phenyl alcohols indicated that the presence of the phenyl group introduced the additional dispersive interactions ( i.e. , London dispersion forces and/or π-stacking 32,33 ) within the chosen materials, the interplay of which with the H-bonding changes along the separation between the phenyl and hydroxyl moieties.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is commonly observed in dielectric measurements of aliphatic MAs, irrespective of the position of hydroxyl units in the molecule. According to the current knowledge, the dynamic properties of the D process for associating liquids are an emanation of their complex internal structure driven by the formation of various supramolecular clusters through hydrogen bonds (HBs). However, the exact molecular origin of this characteristic polarization decay is still yet to be addressed. , Herein one can briefly mention that there are several possible explanations for the nature of this process. Among them, the transient chain model (TCM) proposed by Gainaru and co-workers provides the most commonly accepted description of the molecular origin of the D relaxation. The model postulates that the D mode appears due to changes in the dipole moment associated with the attachment and detachment of molecules to the ends of the H-bonded chains.…”
Section: Introductionmentioning
confidence: 99%
“…All these features allow us to classify monohydroxy alcohols as a convenient model to study the self-assembly phenomenon, driven mainly by noncovalent interactions such as hydrogen bonds, steric effects, electrostatic interactions, or hydrophobic and hydrophilic effects. Consequently, the impact of different factors on the self-assembly phenomenon, architecture of aggregates, and mechanism of their formation can be gained. These clear advantages of MA resulted in publication of numerous articles on these systems where different experimental and theoretical methods including broadband dielectric spectroscopy were applied. , However, these investigations mostly focus on aliphatic monoalcohols in the bulk phase.…”
Section: Introductionmentioning
confidence: 99%